Phát huy vai trò của trí thức nữ Việt Nam trong thời kỳ đổi mới. - Võ, Thị Hồng Loan (2011)
Tác giả: Võ Thị Hồng Loan, ThS; Hoàng Chí Bảo, GS,TS; Nguyễn Chí Dũng, PGS,TS; Nguyễn Văn Đoàn, ThS -- Từ khóa: Trí thức; Bình đẳng giới